2016
DOI: 10.1128/cvi.00399-16
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Parenterally Administered, Structure-Based Rationally Modified Recombinant Staphylococcal Enterotoxin B Protein Vaccine, STEBVax

Abstract: S everal staphylococcal enterotoxins (SEs) are bacterial superantigens (SAgs) produced by Staphylococcus aureus. The serologically and genetically distinct SEs (A, A1, A2, B, C, C1, C2, C3, D, E, G, H, and I) bind to major histocompatibility complex class II (MHC-II) proteins and to T-cell antigen receptors (TCRs), bypassing processing by antigen-presenting cells (1). Since T-cell engagement with SAgs is independent of clonal specificity, picomolar concentrations of a SAg can result in the polyclonal activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 31 publications
(41 reference statements)
0
28
0
Order By: Relevance
“…Vaccines are promising alternatives to antibiotics; however, antistaphylococcal vaccine development has not yet been successful in humans. Seven investigational S. aureus vaccines are currently undergoing development ( Table ). In this review, focus is placed on two of the seven investigational S. aureus vaccines that have reached advanced clinical trials (developed by GSK and Pfizer).…”
Section: Approaches To Developing Vaccines To Prevent Surgical‐site Imentioning
confidence: 99%
“…Vaccines are promising alternatives to antibiotics; however, antistaphylococcal vaccine development has not yet been successful in humans. Seven investigational S. aureus vaccines are currently undergoing development ( Table ). In this review, focus is placed on two of the seven investigational S. aureus vaccines that have reached advanced clinical trials (developed by GSK and Pfizer).…”
Section: Approaches To Developing Vaccines To Prevent Surgical‐site Imentioning
confidence: 99%
“…To date, a TSST-1 toxoid (double mutant G31R-H135A) and an SEB toxoid (triple mutant L45R-Y89A-Y94A), both supplemented with aluminum hydroxide adjuvant, have been tested in phase 1 clinical trials. Both studies showed the vaccines to be safe and well tolerated among healthy vaccines (Table 1) [48,49]. Moreover, both toxoids were still immunogenic and induced a neutralizing antibody response.…”
Section: Vaccination Against Sagsmentioning
confidence: 94%
“…On that basis, inactivating mutations have been predicted and experimentally confirmed for a number of staphylococcal SAgs [45][46][47]. The development of detoxified SEB and TSST-1 mutants is most advanced [48,49]. An effective vaccine against SAgs would encompass the detoxified antigen in combination with adjuvants that stimulate a robust antibody response necessary for direct neutralization of the toxin and an appropriate T cell response targeted at clearing the pathogen [50].…”
Section: Vaccination Against Sagsmentioning
confidence: 99%
“…Since October, the results on safety and immunogenicity of two additional staphylococcal vaccine studies have been published: one applying modified recombinant staphylococcal B protein [21], the other applying a single-dose 4-antigen or 3-antigen Staphylococcus aureus vaccine in healthy adults [22].…”
mentioning
confidence: 99%